2007
DOI: 10.1073/pnas.0702133104
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of olfactory receptor genes inDrosophilaspecies

Abstract: Olfactory receptor (OR) genes are of vital importance for animals to find food, identify mates, and avoid dangers. In mammals, the number of OR genes is large and varies extensively among different orders, whereas, in insects, the extent of interspecific variation appears to be small, although only a few species have been studied. To understand the evolutionary changes of OR genes, we identified all OR genes from 12 Drosophila species, of which the evolutionary time is roughly equivalent to that of eutherian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 36 publications
5
107
0
Order By: Relevance
“…This observation suggests that the more gene duplications occur, the more IGHV pseudogenes are generated in the IGHV multigene family. Previously, Nei and coworkers (Nei et al 1997;Nei and Hughes 1992;Nei and Rooney 2005;Nozawa and Nei 2007) showed that in many multigene families, gene duplication often occurs, but because of deleterious mutations, many duplicate genes become nonfunctional and either stay in the genome as pseudogenes or are gradually eliminated from the genome by unequal crossing over. Although the number of deleted IGHV pseudogenes cannot be assessed easily, our results suggest that throughout IGHV evolution, the numbers of functional and nonfunctional genes are maintained by birth-and-death evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that the more gene duplications occur, the more IGHV pseudogenes are generated in the IGHV multigene family. Previously, Nei and coworkers (Nei et al 1997;Nei and Hughes 1992;Nei and Rooney 2005;Nozawa and Nei 2007) showed that in many multigene families, gene duplication often occurs, but because of deleterious mutations, many duplicate genes become nonfunctional and either stay in the genome as pseudogenes or are gradually eliminated from the genome by unequal crossing over. Although the number of deleted IGHV pseudogenes cannot be assessed easily, our results suggest that throughout IGHV evolution, the numbers of functional and nonfunctional genes are maintained by birth-and-death evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Putative functional and nonfunctional members of these families in the 12 genomes have been comprehensively identified by sequence similarity algorithms (Guo and Kim, 2007;Nozawa and Nei, 2007;Vieira et al, 2007;Gardiner et al, 2008). In some cases, the uncovered genome sequence has been confirmed by DNA re-sequencing (for example, McBride and Arguello, 2007).…”
Section: Genomic Organisation and Phylogenetic Analysismentioning
confidence: 99%
“…Candidate-gene approach to chemosensory speciation: Since the identification of the chemoreceptor gene repertoire of D. melanogaster (Robertson et al, 2003), several studies have exploited this new opportunity to decipher the molecular and physiological basis of signal integration (for example, Dekker et al, 2006;Kurtovic et al, 2007) and the evolutionary dynamics of chemoreceptor genes (Guo and Kim, 2007;Nozawa and Nei, 2007;Tunstall et al, 2007). It is likely that the genes underlying chemosensory habitat and mate preferences that cause premating isolation are to be found among these chemoreceptor-encoding and chemoreceptor-related genes.…”
Section: Genetics Of Divergence In Chemosensory Preferencesmentioning
confidence: 99%